MYASTHENIA GRAVIS COMPLICATING PREGNANCY - Kaluarachchi, A; Abeywickrama, L M (My University, 2012)
Myasthenia gravis is an auto immune disorder characterised by variable weakness m d rjngabiiir;- crt skeletal muscle. This is a rare disease with an incidence of 02 to 10 individuals /100,000. This is more common in women and usually has its onset in 2nd or 3rd decades. We report two cases of myasthenia gravis complicating pregnancy managed at professorial unit of Obstetrics and Gynaecology, Faculty of medicine, Colombo.